THE IMPORTANCE, PERFORMANCE ANALYSIS, SERVICE QUALITY AND PRICE OF MAXIM APPLICATION TOWARDS MANADO USERS - Pasambuna, Veromita C.; Lapian, Stanss L. H. V. J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
The purpose of this study was to determine the importance and performance of the Maxim Application service quality in Manado and to determine the importance and performance of the maxim application price in Manado. This type of research is descriptive research with a quantitative approach. The researcher tries to describe and explain how important and the performance of the Maxim application is. A quantitative approach is applied through a questionnaire. To determine the number of samples, the researcher uses a sampling technique for an unlimited number of people. The sample consists of 100 respondents. Data was collected online and questionnaires. Respondents were classified by gender, age, and occupation as part of the questions in the questionnaire. The results of the study show how important these attributes are and how the performance of the attributes is the same for both service quality and price provided by the company. Conclusions are drawn using the IPA (Importance Performance Analysis) tool to relate the importance and value of performance. Researchers give advice to companies in order to improve service quality and even provide a reasonable price based on the results.Â Keywords: the importance, performance analysis, service quality, price